2022
DOI: 10.1093/trstmh/trac037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anaemia and its associated factors among lactating mothers in eastern Sudan: a cross-sectional study

Abstract: Background Lactating mothers are susceptible to anaemia. Little published data are available on lactational anaemia in Africa, including Sudan. This study was conducted to assess the prevalence of and associated factors for anaemia among lactating mothers in eastern Sudan. Methods A cross-sectional study was conducted and sociodemographic and clinical characteristics were gathered through a questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Nevertheless, another factor that has been linked to anaemia in women is employment. In line with a previous study [16,21], our study found that lactating mothers who were employed had lower odds of having anaemia.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, another factor that has been linked to anaemia in women is employment. In line with a previous study [16,21], our study found that lactating mothers who were employed had lower odds of having anaemia.…”
Section: Discussionsupporting
confidence: 93%
“…Sociodemographic characteristics play a significant role in determining anaemia. Likewise, in other studies, lactating mothers who were employed had lower odds of having anaemia [ 28 , 34 ]. This might be due to their better decision-making autonomy resulting from their financial contributions to family, which empowered them to purchase a variety of foods and seek health facilities [ 28 ].…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, high prevalence of anaemia among lactating women was noticed in many studies conducted in Bangladesh (48%) [ 10 ], Sierra Leone (53%) [ 33 ], Mozambique (53%), Tanzania (46%), Kenia (44%) [ 3 ]. Conversely, a lower prevalence also observed in East Africa (36%), Rwanda (19%) [ 34 ], and Ethiopia (22%) [ 28 ]. Regarding the levels of anaemia status, moderate to severe anaemia was more prevalent among pregnant, and lactating women than adolescent girls.…”
Section: Discussionmentioning
confidence: 99%